1994
DOI: 10.1111/j.1365-263x.1994.tb00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal ligament injection in the dog primary dentition: spread of local anaesthetic solution

Abstract: Summary. The spread of local anaesthetic solution administered with a pressure syringe has not been studied as extensively in young animals having primary or mixed dentitions as in adult animals. The purpose of this investigation was to study the distribution of local anaesthetic solution injected into the periodontal ligament of young dogs. India ink was added to carpules containing 2% lidocaine and 1:100,000 epinephrine, and the spread of solution was examined macroscopically and microscopically. Injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…In particular, these cell populations were substantially higher in the submucosal and intraligamentous PGE2 groups than in the intravenous PGE2 and control groups, a result that also agrees with previous findings 13,14,22. The more substantial increase in the cell populations in the intraligamentous PGE2 group may be attributable to both the increased PGE2 concentration in the PDL21,29 and the diffusion of the intraligamentally applied solution within the PDL,26 from where it passes subperiosteally at the level of the alveolar crest and proceeds along the vascular canals to reach and act directly on the bone marrow.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In particular, these cell populations were substantially higher in the submucosal and intraligamentous PGE2 groups than in the intravenous PGE2 and control groups, a result that also agrees with previous findings 13,14,22. The more substantial increase in the cell populations in the intraligamentous PGE2 group may be attributable to both the increased PGE2 concentration in the PDL21,29 and the diffusion of the intraligamentally applied solution within the PDL,26 from where it passes subperiosteally at the level of the alveolar crest and proceeds along the vascular canals to reach and act directly on the bone marrow.…”
Section: Discussionsupporting
confidence: 90%
“…Lidocaine might reduce the pain caused by the injection of PGE2, itself a pain mediator. The consensus in dentistry is that intraligamentous application of an active substance through a pressurized syringe is reliable and safe 25,26. The American Dental Association Council on Dental Materials, Instruments, and Equipment characterized intraligamentous injection as being "an effective method, sufficient for pulpal anesthesia in dental operations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were few studies that reported the tissue distribution of local anesthetic after regional injection into oral tissue. Tissue specimens of dogs were observed 15 minutes, 12 hours, and 5 days after administration of a mixture of 2% lidocaine containing 1:100,000 epinephrine and India ink, injected into the periodontal ligament space 14,15) . However, these studies did not investigate the tissue distribution of local anesthetics shortly after regional injection.…”
Section: Introductionmentioning
confidence: 99%